Factors associated to antidepressant prescription for civil servants of Belo Horizonte, MG - Renato Lopes Hurtado; Sérgia Maria Starling Magalhães; Andréia Queiroz Ribeiro; Micheline Rosa da Silveira (Universidade de São Paulo, 2010)
Selecting the most suitable drug for the treatment of depression has clinical and economic implications, since both safety and cost of antidepressants (AD) vary among therapeutic subgroups. This study aimed to evaluate the prescription of antidepressants for users of the pharmacy for civil servants of PBH (FARMASERV) in 2005. Univariate, bivariate and multivariate analyzes using logistic regression were performed. Of the total prescriptions analyzed (652), the majority were for women (81.7%) and individuals aged between 19 and 59 years (81.7%). The variables independently associated with the selection of AD were gender, age and the specialty of the prescriber. Women and young adults were more likely to be prescribed an SSRI compared to their congeners, with statistically significant differences. Psychiatrists were more likely to prescribe an SSRI than neurologists or general physicians. The determinant factors for selecting antidepressants may aid the planning of interventions aimed at patients and prescribers which can enable rationalization of the use of antidepressants. A seleção adequada do medicamento para o tratamento da depressão tem implicações clínicas e econômicas, visto que a segurança e o custo dos antidepressivos (AD) variam entre as subclasses terapêuticas. Esse estudo avaliou prescrições de AD dispensadas em 2005 para usuários da Farmácia da Clínica dos Servidores da PBH (FARMASERV). Foram realizadas análises univariada, bivariada e multivariada dos dados, utilizando-se regressão logística. Do total de prescrições (652), a maioria era para mulheres (81,7%) e para indivíduos com idade entre 19 e 59 anos (81,7%). As variáveis independentemente associadas à seleção de AD foram gênero, faixa etária e especialidade do prescritor. Mulheres e adultos jovens têm maior chance de receber prescrição de ISRS, em comparação aos seus congêneres, sendo as diferenças estatisticamente significativas. A chance dos psiquiatras prescreverem ISRS é maior do que neurologistas e clínicos gerais. Os fatores determinantes da seleção do antidepressivo podem subsidiar o planejamento de intervenções dirigidas aos pacientes e prescritores de forma a permitir a racionalização de sua utilização.